Underground Mine Tunnel Modelling Using Laser Scan Data in Relation to Manual Geometry Measurements - Jakub Janus; Piotr Ostrogórski (Energies, 2022)
Underground mine tunnels, drifts, and mine headings are susceptible to the impact of convergence. The convergence has a big influence on further measurements such as airflow and the volume concentration of methane and other gases. In most cases, deformation of arch supports lead to getting a smaller cross-section area. A comparison is made between five methods of measuring the cross-sectional area of a mine tunnel. The reference size of the six cross-section mine drift areas were obtained by Terrestrial Laser Scanning, which were then compared with the cross-section areas obtained by four other methods. The following methods were considered: area calculation using CAD software, an empirical method, approximation by a semi-ellipse and approximation by a semi-ellipse with attached straight sections. This article presents the quantitative and qualitative differences of the obtained results. Differences in the calculated cross-sectional areas of the mine drift are discussed, and reasons for the differences are determined. In addition, the advantages and disadvantages of each method are indicated.